2018
DOI: 10.1590/1981-6723.01617
|View full text |Cite
|
Sign up to set email alerts
|

Effect of infield handling conditions and time to pre-cooling on the shelf-life and quality of tomatoes

Abstract: This study investigates the effects of post-harvest handling practices prior to storage on the quality of tomatoes in South African supply chains. Pink mature tomatoes were harvested in the morning and afternoon, transported from two farms located 40 km apart to two central pack houses located near each of the farms in Limpopo, South Africa. The samples were transported using bins (468 kg capacity) and lugs (20 kg capacity). After harvesting, the samples were either immediately transported to the pack house an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
16
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 24 publications
(20 citation statements)
references
References 19 publications
4
16
0
Order By: Relevance
“…It has been reported that the cooling temperature (20°C) can promote a delay in the weight loss and an increase in the shelf life of tomatoes fruit storage postharvest. This observation is seen in a previous report 51 in which the storage temperature conditions played an important role in determining the rate of ripening and degradation of fresh fruits.…”
Section: Resultssupporting
confidence: 84%
“…It has been reported that the cooling temperature (20°C) can promote a delay in the weight loss and an increase in the shelf life of tomatoes fruit storage postharvest. This observation is seen in a previous report 51 in which the storage temperature conditions played an important role in determining the rate of ripening and degradation of fresh fruits.…”
Section: Resultssupporting
confidence: 84%
“…A decrease in values of h°and L* both were indicative of the green to red color change with storage period as the fruit ripens. Cherono et al (2018) had similar observation of color changes with storage time where the h°value significantly reduced between sampling days 0, 4, 8, and 16 though there was no significant variation between day 16 and day 24 of sampling. Zakari et al (2016) on their work on EC made observed that the tomatoes changed from yellowish red to a deep-red color by the sixth day of storage.…”
Section: Tomato Firmnessmentioning
confidence: 55%
“…The chromo meter was calibrated with a white paper before taking measurements at day 0, day 7, day 14, day 21, and day 28. Each sampled tomato was measured for L*, a* and b* at three equatorial positions (blossom end, stem-end, and mid-way), which were averaged to determine the overall values using the procedure by Cherono, Sibomana, and Workneh (2018). The values are based on a reference scale where a* ("+" value indicated redness and "−" value indicated greenness), b* ("+" value indicated yellowness and "−" value indicated blueness) and L* (varies from 0 to 100 where "100" indicated white and "0"indicated black).…”
Section: Colourmentioning
confidence: 99%
See 1 more Smart Citation
“…The extracted juice was filtered using a muslin cloth. A total of 36 readings per day (2 × 18 replicates) of total soluble solids were determined from all treatments by adding one to two clear drops of the juice on the prism surface of the digital refractometer (Model: PR-32 α, ATAGO Co., Ltd., Tokyo, Japan), presented as • Brix [23]. Previously prepared juice was used to measure lycopene and carotenoid pigments and both were determined by using the spectrophotometric method as explained by Munhuewyi [24].…”
Section: Determinations Of Weight Loss Firmness and Colormentioning
confidence: 99%